The Probe Team [episode no. 272] - Lazaro, Cheche (Probe Productions, 1993)
The first part presents the cry for justice of victims, Levi and Alvin Vinculado in Bulacan. A female functional literacy program launched by UNICEF together with DECS in Maguindanao is presented in the second part of the tape. The third part is a one-on-one interview with a famous saxophone player.